Absence of oral nutritional support in low food intake inpatients is associated with an increased risk of hospital-acquired pressure injury. (October 2022) - Papier, Irena; Sagi-Dain, Lena; Chermesh, Irit; Mashiach, Tanya; Banasiewicz, Tomasz
Summary: Background & aims: Hospital-acquired pressure injury (HAPI) incidence is a common burden in hospitals. Decreased food intake leading to malnutrition compromises body tissues involved in pressure injury occurrence. However, most tools for predicting pressure injuries do not include daily food intake monitoring nor consider further nutritional interventions. This study aimed to investigate clinical practices for food intake monitoring and its association with predicting HAPI risk, together with Norton Scale use, and whether the initiation or absence of oral nutritional supplements (ONS), separately from other nutritional interventions, was associated with HAPI incidence in low food intake inpatients, who consumed less than 50% of requirements. Methods: This observational cohort study covered a one-year period (08/2018–07/2019). Demographic and clinical data were extracted from computerized files of patients hospitalized ≥7 days, aged ≥60 years, and who ate orally. Patients receiving enteral or parenteral nutrition were excluded. Differences were studied between groups without and with HAPI grade ≥2. Subgroups divided by Norton Scale and intake, Norton Scale and albumin levels, food intake and initiation (or not) of any nutritional intervention versus ONS only, were examined for the consistency of association with HAPI. Results: Of the 5155 admissions during the study period, 895 patients fulfilled the inclusion criteria: 48% female, mean age 77.6 ± 9.1 years, 11% with MUST score ≥2. Nutritional intake was reported in 76% of patients, of them 22% had low food intake, and 9% of the study group developed HAPI grade ≥2. Regarding HAPI incidence, no differences were found between groups divided by MUST scores. Independent risk factors significantly associated with HAPI were Norton <14, albumin levels <3 g/dl, and low food intake. Not providing ONS in low food intake patients had an adjusted 3.49-fold (95%CI 1.57–7.75) increase in HAPI risk (6-fold for non-adjusted relative risk). Conclusion: Failure to initiate ONS as part of nutritional support in low food intake patients is associated with high HAPI risk in these patients. Consequently, monitoring of daily food intake for identifying low intake patients should be integrated into routinely used tools such as the Norton Scale, and adherence to nutritional protocols should be addressed.